Cultivar, sowing density, or time of emission: What influences mortality and performance of wheat tillers the most? (Revista de Ciências Agroveterinárias, 2021)
The emission and survival of wheat tillers can be influenced by several factors. This study  aimes to evaluate the influence of sowing density, tillering potential, and temporal order of emission on the survival, and performance of individual tillers by contrasting the tillering potential of wheat cultivars. The experiment design consisted of a randomized block design with four replications, in a 2×4 factorial scheme, consisting of two wheat cultivars (TBIO Toruk and TBIO Sossego) and four sowing densities (208, 312, 416, and 500 viable seeds m−2). Tillers were identified weekly, according to the temporal order of emission, for four consecutive weeks. The study evaluated emission, survival, and productive performance of all tillers, in addition to plant height, peduncle length, stem diameter, fresh weight, and presence of grains. The overall mortality of emitted tillers was 24%. A decrease of 73% in emission and 92% in tiller survival was observed over a period of four weeks. The increased sowing density led to a decrease of 43% in emission and 44% in tiller survival. The cultivar Sossego presented less tillering potential, but with higher survival rate than Toruk. The first two emitted tillers represented 77% of the total emitted tillers. Surviving tillers emitted in the first week were responsible for 40% of the total presence of grains at the end of the wheat cycle.
Keywords: Triticum aestivum; tillering potential; time of emission